Software for computer control : proceedings of the second IFAC/IFIP Symposium on Software for Computer Control, Prague, Czechoslovakia, 11-15 June 1979 - Novak, M. (Published for the International Federation of Automatic Control by Pergamon Press, 1979)
Software for Computer Control is a collection of papers and lectures presented at the Second IFAC/IFIP Symposium on Software for Computer Control, held in Prague, Czechoslovakia in June 1979. The symposium is organized with the hope of making vital contributions to the development of the computer sciences.